Speech by Y.A.B. Dr Lim Chong Eu at the Barisan Nasional headquarters on Sunday 10th October 1976 At 4.30 p.m. - Lim, Chong Eu (1976)

(untitled)
On behalf of the members of the Barisan Nasional State of Penang,I welcome Y.A.B Perdana Menteri on his visit to the Barisan Nasional Headquarters to meet members of the State Barisan Nasional in his capacity as National President of the organisation.